PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KEPUASAN KERJA YANG BERIMPLIKASI PADA KINERJA KARYAWAN DI PT. MASCHIL SUKSES MAKMUR (NEW VISION) - Joonner Rambe; Isnaria Isnaria (Jurnal Manajemen FE-UB, 2018)
This study aims to determine the extent to which the leadership style, motivation for employee performance through job satisfaction at PT. Maschil Success Makmur (New Vision).The data used in this study in the form of primary data collected from respondents' answers based on questionnaires given, ie as many as 113 people. Data processing method using path analysis method (Path Analysis) with the help of SPSS version 21.0. The statistical test used the significance test of individual parameters (t test) and simultaneous significance test (Test F).The results showed that simultaneously the variables, leadership style, motivation and job satisfaction had a significant effect on employee performance. Partially showed that analysis 1: the influence of leadership variable significantly influence the employee performance, while the 2: motivation variables significantly influence the employee performance and on the analysis 3: job satisfaction variable has a significant effect on employee performance. Keywords: Leadership style, Motivation, Job Satisfaction and Employee Performance